Interfacial interactions in electrospun PVA-MC/MXene nanofibers: A route to enhanced dielectric and antimicrobial properties - Erol, Ibrahim; Ismail, Ibrahim; Hazman, Omer; Demirelli, Kadir; Guney, Bekir (Elsevier, 2026)
This study comprehensively investigates the structural, electrical, biological, and functional properties of electrospun PVA-MC/MXene fiber nanocomposites prepared by incorporating MXene into a polyvinyl alcohol (PVA)-methyl cellulose (MC) matrix. The inclusion of MXene notably refined the fiber morphology, reducing the average diameter from 214 nm to 86 nm at a 5 wt% MXene concentration. EDX-MAP analyses confirmed homogeneous elemental distribution at 5 wt%, while Ti clustering was observed at 10 wt%. Surface characterization revealed enhanced hydrophilicity, with the contact angle decreasing from 55.2 degrees to 49.2 degrees and total surface free energy increasing from 59.02 mN/m to 64.33 mN/m. Thermal analyses indicated improved stability, as the onset degradation temperature rose from 290 degrees C to 315 degrees C and the glass transition temperature from 110 degrees C to 121 degrees C. The dielectric constant (epsilon') increased to 10.5 with 10 wt% MXene, consistent with interfacial polarization governed by the Maxwell-Wagner-Sillars mechanism. AC conductivity improved from 10(-8) S/cm at 10(3) Hz to 10(-5) S/cm at 10(6) Hz. Biologically, DPPH radical scavenging efficiency reached 53 %, showing a similar to 20 % enhancement over pristine PVA-MC. Antimicrobial activity also increased, with inhibition zones expanding from 12 mm to 15 mm for E. coli and from 9 mm to 14 mm for C. albicans. Overall, PVA-MC/MXene nanocomposites exhibit superior dielectric, thermal, and biological characteristics, making them promising candidates for applications in energy storage, biomedical coatings, wound dressings, smart sensors, and filtration systems.
Keywords: PVA; Methyl cellulose; MXene; Dielectric properties; Antimicrobial activity